Evaluation of an Antioxidant and Anti-inflammatory Cocktail Against Human Hypoactivity-Induced Skeletal Muscle Deconditioning - Arc-Chagnaud, Coralie; Py, Guillaume; Fovet, Théo; Roumanille, Rémi; Demangel, Rémi; Pagano, Allan F.; Delobel, Pierre; Blanc, Stéphane; Jasmin, Bernard J.; Blottner, Dieter; Salanova, Michele; Gomez-Cabrera, Mari-Carmen; et al. (Frontiers in Physiology, 2020)
Understanding the molecular pathways involved in the loss of skeletal muscle mass and function induced by muscle disuse is a crucial issue in the context of spaceflight as well as in the clinical field, and development of efficient countermeasures is needed. Recent studies have reported the importance of redox balance dysregulation as a major mechanism leading to muscle wasting. Our study aimed to evaluate the effects of an antioxidant/anti-inflammatory cocktail (530 mg of polyphenols, 138 mg of vitamin E, 80 µg of selenium and 2.1 g of omega-3) in the prevention of muscle deconditioning induced by long-term inactivity. The study consisted of 60 days of hypoactivity using the head-down bed rest (HDBR) model. Twenty healthy men were recruited; half of them received a daily antioxidant/anti-inflammatory supplementation, whereas the other half received a placebo. Muscle biopsies were collected from the vastus lateralis muscles before and after bedrest, and 10 days after remobilization. After 2 months of HDBR, all subjects presented muscle deconditioning characterized by a loss of muscle strength and an atrophy of muscle fibers, which was not prevented by cocktail supplementation. Our results regarding muscle oxidative damage, mitochondrial content and protein balance actors refuted the potential protection of the cocktail during long-term inactivity and showed a disturbance of essential signaling pathways (protein balance, mitochondriogenesis) during the remobilization period. This study demonstrated the ineffectiveness of our cocktail supplementation and underlines the complexity of redox balance mechanisms. It raises interrogations regarding the appropriate nutritional intervention to fight against muscle deconditioning.